Efecto de medios nutricionales con trichoderma harzianum y tiempo de fermentación en crecimiento y desarrollo en cultivo de pimiento. - Pacheco Quizhpe, Anthony Ramiro; Quezada Salazar, Brithany Suleika (Machala : Universidad Técnica de Machala, 2023)
The bell pepper (Capsicum annuum L.) is a highly important vegetable worldwide, with a global production of 36,972,494 tons in 2022. China, Mexico, Indonesia, Turkey, and Spain lead production. In Ecuador, bell pepper is essential and cultivated in various regions, although its production has declined in the province of El Oro due to climatic, anthropogenic, and soil pathogen factors. This study aimed to evaluate the effect of nutritional media with Trichoderma harzianum at different fermentation times on the growth of bell pepper seedlings under normal and water-stress conditions. The study was conducted at the experimental farm of the "Santa Inés" campus of the Technical University of Machala, El Oro. A completely randomized design (CRD) with 19 treatments and 4 replications was used to evaluate the effect of combinations of Potato, Rice Husk, Oat with Molasses, Dextrose, and Trichoderma on the plants. Results showed that, under normal conditions, the most effective treatments were Oat + Dextrose + Trichoderma and Oat + Molasses + Trichoderma. Under water-stress conditions, the most effective treatments were Potato + Molasses + Trichoderma, Rice Husk + Molasses + Trichoderma, and Rice Husk + Dextrose + Trichoderma.
El pimiento (Capsicum annuum L.) es una hortaliza de gran importancia a nivel mundial, con una producción global de 36,972,494 Toneladas en 2022. China, México, Indonesia, Turquía y España lideran la producción. En Ecuador, el pimiento es esencial y se cultiva en diversas regiones, aunque en la provincia de El Oro su producción ha disminuido debido a factores climáticos, antrópicos y patógenos del suelo. Este ensayo tuvo como objetivo evaluar el efecto de medios nutricionales con Trichoderma harzianum en diferentes tiempos de fermentación sobre el crecimiento de plántulas de pimiento bajo condiciones normales y de estrés hídrico. El estudio se llevó a cabo en la granja experimental del campus "Santa Inés" de la Universidad Técnica de Machala, El Oro. Se utilizó un diseño completamente al azar (DCA) con 19 tratamientos y 4 repeticiones, evaluando el efecto de combinaciones de Papa, Arrocillo, Avena con Melaza, Dextrosa y Trichoderma en las plantas. Los resultados mostraron que, bajo condiciones normales, los tratamientos más efectivos fueron Avena + Dextrosa + Trichoderma y Avena + Melaza + Trichoderma. Bajo condiciones de estrés hídrico, los tratamientos más eficaces fueron Papa + Melaza + Trichoderma, Arrocillo + Melaza + Trichoderma y Arrocillo + Dextrosa + Trichoderma.
Keywords: TRICHODERMA; PIMIENTO; FERMENTACION MEDIOS NUTRICIONALES